Optimization of gas tungsten Arc welding (GTAW) process for heat exchanger in offshore structure [electronic resource] - Amin Mumini Muhamad, 1985- (2008)
Project Paper (Sarjana Muda Kejuruteran (Mekanikal - Bahan)) - Universiti Teknologi Malaysia, 2008